Costos de producción como medio para establecer la rentabilidad en la empresa industrial “Palma” de la parroquia la Unión, año 2014.” - Zambrano Delgado, Doris Matilde (2015)
This research was conducted in the industrial workshop "Palma", the same that is dedicated to the matalurgica activity, to the elaboration of doors, windows and all kinds of lattices, whose overall objective is to determine production costs as a means of establishing the profitability of industrial company "Palma" in paroquia "La Union" in 2014 year, for the development of the thesis were used the methods, descriptive, inductive and analytical, the same that led to the achievement of this research were used and made it clearer and analytical. The Data were collected using interviews or surveys to the own workers as well as direct observation was the best contribution to achieve, the objectives of the feedback, interviews and surveys, it notes that the company does not realize any sitema costing, by accounting records, for that this work generate an accounting manual system with the manual cost elementes ando somo finantial indicators for the company to apply them, will serve for decision-making and to establish its profit margins by product lines It should be noted that the company Industrial workshop "Palma" does not have the equipment and conditions for their peratividad and safety. To develop the system of production costs orders was determined that the cost of developing a protector is $ 254.44 on a cover of $ 1,311.31, $ 369.11 a cart, a basket and a door $ 171.88 $ 463.34. The point of balance even break even product is to: 35 guards, 1 indoor and 19 doors; to assess the contribution of each product favorable trends were detected with respect to the elaboration of roofing and carts, There should be a setting in the selling price.